(untitled) (Journal of Engineering Studies and Research, 2020)
The integration between catalytic chemistry and reaction engineering fields generate more efficient catalytic reactor designs whereby the conventional design strategies should be changed. This work evaluated the implications on preliminary fixed bed catalytic reactor design and its associated basic cost from bench-scale when it is considered the material balance at microscale under a deterministic model accompanied with heuristic considerations on equipment design showing that understanding chemical reaction engineering is key to design of more efficient and economical industrial processes (decrease in 50 % of equipment sizing and 40 % of the equipment cost for this study).